Accounting conservatism, business strategy, and ambiguity - Hsieh, Chia-Chun; Ma, Zhiming; Novoselov, Kirill E. (Accounting, Organizations and Society, 2019)
We investigate whether accounting conservatism can be explained as a rational response to ambiguity. Decision analysis shows that decision rules that work well under ambiguity put greater weight on negative than on positive outcomes, i.e., exhibit caution. Accounting conservatism increases the timeliness of bad news that is more relevant under cautious decision rules and thereby helps corporate managers and investors implement them. We, therefore, hypothesize that firms facing greater ambiguity report more conservatively. We adopt two different measures to proxy for the firm-specific level of ambiguity. First, we identify firms pursuing the “prospector” versus “defender” business strategies. Compared with defenders, who focus on utilizing existing resources, prospectors actively create their future by seeking new business opportunities and thus face greater ambiguity. Second, we conduct an additional set of tests based on environmental scanning, which reduces ambiguity. Both sets of results suggest that firms facing greater ambiguity report more conservatively.